The Effect of Organizational Culture, Team Collaboration, and Work Motivation on the Performance of Health Workers in Cahaya Bunda Mother and Child Hospital - Cindy Thiovany Soetomo; Made Favian Budi Gunawan; Kelvin Fernaldi; Halimah Hasan (Universitas KH. Abdul Chalim Mojokerto, 2025)
Cahaya Bunda Mother and Child Hospital in Bali is dedicated to improving healthcare standards for mothers and children, focusing on reducing maternal and infant mortality rates. The performance of healthcare workers is a critical factor in achieving optimal patient outcomes, particularly in specialized hospitals such as mother and child hospitals. However, health worker performance is influenced by various factors, including organizational culture, team collaboration, and work motivation. This study aims to analyze the individual and collective effects of these factors on health worker performance. Using a quantitative approach, data were collected through a structured questionnaire distributed to 34 nurses and midwives. SmartPLS 3.2 software was employed for analysis. The findings reveal that work motivation significantly impacts health worker performance, underscoring its critical role in driving effectiveness and commitment to healthcare services. Conversely, organizational culture and team collaboration showed no statistically significant effects on performance, which may be attributed to sample size limitations and contextual factors within the hospital environment. The study highlights that while a supportive culture and collaborative environment are essential, intrinsic motivation remains a key driver of performance outcomes. This research contributes to understanding how motivation directly influences healthcare workers’ productivity, while organizational culture and team collaboration provide a foundation that indirectly supports performance. Future studies should explore the interplay between these factors to develop targeted strategies for optimizing healthcare delivery in specialized settings like mother and child hospitals.